Jade line spraying-free process

By preparing specific color masterbatches and adding functional additives, combined with molding technology, the spray-free jade pattern effect of plastic products is achieved, solving the problems of complex equipment, high cost and poor durability of traditional spraying processes, and improving the mechanical properties and aesthetics of the product.

CN119591978AActive Publication Date: 2025-03-11FUJIAN HUASU NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411924738.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Traditional spraying technology is difficult to achieve natural, smooth and distinctly layered jade texture on plastic products, and there are problems such as complex equipment, high cost, environmental pollution and poor durability.

Method used

By preparing specific masterbatches and adding functional additives, combined with molding technology, the spray-free effect of jade patterns is achieved through injection molding and polishing. The raw materials for preparing masterbatches include carrier resins, colorants, antioxidants, lubricants, light stabilizers, tougheners and inorganic particles. Modified graphene oxide and specific copolymers are used as tougheners and compatibilizers to improve the wear resistance and mechanical properties of the material.

Benefits of technology

It realizes that without using additional spraying processes, plastic products show natural and smooth and distinctly layered jade texture, while improving the mechanical strength, weather resistance, wear resistance and color durability of the product, and is suitable for high-end decorative materials and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of plastic products, and particularly relates to a spraying-free process for jade lines. The spraying-free process for the jade grains comprises the following steps: uniformly mixing raw materials, performing injection molding, and polishing the surface. According to the invention, the specific color master batch is prepared, the functional additive is added, and the molding technology is combined, so that the final product can show natural, smooth and well-layered jade texture under the condition of not using an additional spraying process. According to the method, the production process is greatly simplified, the cost is reduced, and meanwhile, the problem of environmental pollution possibly generated in the traditional spraying process is also avoided. In addition, the product prepared by adopting the technical scheme provided by the invention has good mechanical strength, weather resistance, wear resistance and color durability, and is suitable for the fields of high-end decorative materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic products, and in particular relates to a spray-free process for jade patterns. Background Art

[0002] In the field of plastic product processing, giving the product surface a unique decorative effect and texture has always been one of the important goals pursued by the industry. Traditionally, in order to achieve an appearance similar to the texture of natural jade, manufacturers usually use a spraying process, that is, after the plastic product is formed, a coating material containing specific pigments and additives is sprayed, and then dried and cured to form the desired texture and color on the product surface. However, this traditional spraying process has many shortcomings.

[0003] First, the spraying process requires additional equipment and procedures, which increases the complexity and cost of the production process. During the spraying process, the waste of paint, equipment maintenance and energy consumption all constitute a considerable economic burden. Secondly, the spraying process may also cause environmental pollution problems. Volatile organic compounds (VOCs) in the paint are easily volatilized into the atmosphere during the spraying and drying process, causing adverse effects on the environment. In addition, the adhesion and durability of the spray coating are also key factors that restrict product quality. Once the coating peels off or fades, it will seriously affect the appearance and service life of the product.

[0004] In order to solve the above problems, the present invention proposes a spray-free process for jade patterns, aiming to make the final product show a natural, smooth and layered jade texture without using an additional spraying process, while improving the comprehensive performance of the product, providing a better choice for high-end decorative materials and other fields. Summary of the invention

[0005] The purpose of the present invention is to provide a spray-free process for jade patterns. By preparing specific masterbatches and adding functional additives, combined with molding technology, the final product can show a natural, smooth, and layered jade texture without using an additional spraying process, and at the same time has good mechanical strength, weather resistance, wear resistance and color durability.

[0006] A spray-free process for producing jade patterns comprises the following steps: mixing raw materials uniformly, performing injection molding, and polishing the surface to obtain the jade pattern.

[0007] Preferably, the raw materials include base resin, masterbatch and compatibilizer.

[0008] Preferably, the mass of the masterbatch is 1%-20% of the mass of the base resin.

[0009] Preferably, the added amount of the compatibilizer is 1%-3% of the total mass of the base resin and the masterbatch.

[0010] Preferably, the base resin includes one or more of PA, PP, PC, HIPS, ABS, PMMA, ABS / PMMA, TPU, PBT, and POM; further preferably, it is PP.

[0011] The PP is homopolymer PP, with a melt index of 10-15 g / 10 min at 190° C., an isotacticity of ≥95.5%, and a flexural modulus of ≥1300 MPa.

[0012] In some preferred embodiments, the PP is purchased from Dongguan Weicai Plastic Raw Materials Co., Ltd., PPH-M12.

[0013] The masterbatch is prepared from raw materials, by weight, including 60-120 parts of carrier resin, 0.1-0.5 parts of colorant, 0.5-1 parts of antioxidant, 0.5-1.5 parts of lubricant, 0.5-1 parts of light stabilizer, 2-5 parts of toughening agent and 3-8 parts of inorganic particles.

[0014] Preferably, the carrier resin includes one or more of ABS, PP, PE, PS, and PMMA; further preferably, it is PE, PMMA, and ABS.

[0015] Preferably, the mass ratio of PE, PMMA and ABS is 1:(0.5-2):(0.5-2); further preferably, it is 1:1:1.

[0016] Preferably, the PE includes LLDPE and HDPE.

[0017] Preferably, the mass ratio of LLDPE to HDPE is 1:(0.5-2); further preferably, it is 1:1.

[0018] Preferably, the LLDPE has a melt index of 45-55 g / 10 min at 190°C and a density of 0.9-0.95 g / cm 3 , Izod notch impact strength is 45-50kJ / m 2 .

[0019] In some preferred embodiments, the LLDPE is purchased from ExxonMobil, LL6201XR.

[0020] Preferably, the HDPE has a melt index of 28-32 g / 10 min at 190° C., a tensile yield stress of ≥20 MPa, and a flexural modulus of ≥950 MPa.

[0021] In some preferred embodiments, the HDPE is purchased from ExxonMobil, HDPE HMA 018.

[0022] Preferably, the PMMA has a melting index of 15-20 g / 10 min at 230° C., a total light transmittance of ≥92%, and a Rockwell hardness of ≥84.

[0023] In some preferred embodiments, the PMMA is purchased from Qingdao Zhongxin Huamei Plastic Co., Ltd., China, CM-211.

[0024] Preferably, the ABS has a melt index of 2-5 g / 10 min at 200°C, an elongation of 35%-45%, and a bending strength of 600-650 kg / cm 3 .

[0025] In some preferred embodiments, the ABS is purchased from Chi Mei in Taiwan, China, PA-726M.

[0026] PP is selected as the main raw material for plastic products. It is not only lightweight, durable and easy to process, but also non-toxic and odorless, with excellent heat resistance and chemical stability, and good transparency. It can display the color of the masterbatch to the maximum extent. However, its wear resistance is poor, and the addition of masterbatch will affect its mechanical properties. Moreover, the addition of ordinary masterbatch cannot make plastic products show a natural, smooth and layered jade texture without the use of additional spraying process.

[0027] The inventors found that by using specific PE and PMMA as carrier resins to prepare masterbatches and applying them in the field of plastic products, it is possible to achieve a natural jade texture effect without using an additional spraying process, while ensuring the color presentation effect and the mechanical properties of the plastic products. This may be because by selecting raw materials with different melt indexes and controlling their addition amount, the masterbatch can flow smoothly during the injection molding process, simulating a texture effect similar to natural jade. There is a synergistic effect between PE and PMMA. The high strength and rigidity of HDPE provide a solid skeleton for plastic products, while having high gloss and high shape stability. The prepared plastic products are suitable for use in the decoration field. The flexibility and impact resistance of LLDPE enhance the toughness of plastic products. The combination of the two makes the plastic products have good impact resistance while maintaining high strength. The high transparency and gloss of PMMA make the plastic products more beautiful in appearance, improve the transparency of the masterbatch, make the color presented by the plastic products clearer, and make the texture more advanced. At the same time, the addition of PMMA can also improve the surface quality of plastic products and reduce flaws and defects. However, the compatibility between PE and PMMA and PP is poor. Direct mixing may cause uneven distribution of masterbatch in the system, affecting the product effect. In addition, the wear resistance and mechanical properties of plastic products prepared from the masterbatch and PP raw materials are limited, which will affect their lifespan.

[0028] Preferably, the colorant includes dye-type toner, which is not specifically limited and includes but is not limited to organic pigments, inorganic pigments, pearl powder, metal powder, etc.

[0029] Preferably, the antioxidant includes one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 300; more preferably, antioxidant 1010 and antioxidant 168 are included.

[0030] Preferably, the mass ratio of the antioxidant 1010 to the antioxidant 168 is 1:(0.5-2); further preferably, it is 1:1.

[0031] Preferably, the lubricant includes one or more of oxidized polyethylene wax, paraffin, calcium stearate, silicone oil, fatty acid amide, white mineral oil, barium stearate, magnesium stearate, ethylene bis stearamide, and pentaerythritol stearate; further preferably, oxidized polyethylene wax and calcium stearate.

[0032] Preferably, the mass ratio of the oxidized polyethylene wax to calcium stearate is (1-3):1, and more preferably, 2:1.

[0033] Preferably, the kinematic viscosity of the oxidized polyethylene wax at 140°C is 15 to 25 mm 2 / s, and a softening point of 110-120°C; further preferably, the kinematic viscosity of the oxidized polyethylene wax at 140°C is 20.5 mm 2 / s, softening point is 115℃.

[0034] In some preferred embodiments, the oxidized polyethylene wax is purchased from Henan Yuyang Wax Co., Ltd.

[0035] Preferably, the light stabilizer comprises bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0036] Preferably, the toughening agent includes one or more of ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, ethylene-vinyl acetate copolymer, and ethylene-acrylate-glycidyl methacrylate terpolymer; further preferably, ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, and ethylene-vinyl acetate copolymer.

[0037] Preferably, the mass ratio of the ethylene-octene copolymer, the methyl methacrylate-butadiene-styrene copolymer, and the ethylene-vinyl acetate copolymer is (1-3): (1-3): 1; more preferably, it is 2:2:1.

[0038] Preferably, the ethylene-octene copolymer has a melt index of 28-32 g / 10 min at 190° C., is preheated for 1 minute using a large rotor, and rotated at 121° C. for 4 minutes, and has a Mooney viscosity of 1-3 MU.

[0039] In some preferred embodiments, the ethylene-octene copolymer is purchased from Dow Chemical, USA, 8400.

[0040] Preferably, the methyl methacrylate-butadiene-styrene copolymer has a rubber content of 58%-62%, a hydroxyl value of 4-6phr, and an impact strength of 73-75kJ / m at a thickness of 1 / 8 inch. 2 .

[0041] In some preferred embodiments, the methyl methacrylate-butadiene-styrene copolymer is purchased from Japan Kanebuchi, M521.

[0042] Preferably, the melt index of the ethylene-vinyl acetate copolymer at 190°C is 2-3 g / 10 min, the vinyl acetate content is 16%-20%, and the elongation at break is 750-850 MPa; further preferably, the melt index of the ethylene-vinyl acetate copolymer at 190°C is 2.5 g / 10 min, the vinyl acetate content is 18%, and the elongation at break is 800 MPa.

[0043] In some preferred embodiments, the ethylene-vinyl acetate copolymer is purchased from Formosa Plastics Corporation in Taiwan, China, and is EVA SF45TAISOX.

[0044] The inventors found that the use of specific ethylene-octene copolymers, methyl methacrylate-butadiene-styrene copolymers, and ethylene-vinyl acetate copolymers as tougheners can maintain good weather resistance and jade-like effects while enhancing impact resistance and wear resistance. This may be due to the synergistic effect of the three. Ethylene-octene copolymers build an energy absorption network in plastic products with their high elasticity and toughness, effectively disperse and absorb external impact energy, while optimizing the internal structure and reducing defects, laying the foundation for improving wear resistance. Methyl methacrylate-butadiene-styrene copolymers, through their unique microphase separation structure, not only maintain the transparency of plastic products, but also enhance their impact resistance, and can also form a protective film on the surface to improve wear resistance. Ethylene-vinyl acetate copolymers absorb and disperse ultraviolet rays with their good weather resistance and softness, reduce aging phenomena, and maintain the softness and easy processing of plastic products. These three tougheners are intertwined in plastic products to form a multi-level toughening network. Through their interaction, they jointly improve the overall performance of plastic products, enhancing impact resistance and wear resistance while maintaining good weather resistance and jade-like effects. This synergistic mechanism makes plastic products more durable and practical while maintaining their beauty, providing strong support for their application in the field of high-end decoration.

[0045] Preferably, the inorganic particles include one or more of modified graphene oxide, talc, montmorillonite, kaolin, titanium dioxide, silicon dioxide, and calcium carbonate; further preferably, they are modified graphene oxide.

[0046] Preferably, the preparation method of the modified graphene oxide comprises the following steps: taking a coupling agent and hydrolyzing it in an ethanol aqueous solution, then adding graphene oxide, stirring at 55-65° C. for 1-3 hours, vacuum filtering, taking out the powder, heating and drying, and obtaining the modified graphene oxide.

[0047] Preferably, the mass fraction of ethanol in the ethanol aqueous solution is 10%-20%; further preferably, it is 15%.

[0048] Preferably, the volume ratio of the coupling agent to the ethanol aqueous solution is 1:30-50; more preferably, it is 1:40.

[0049] Preferably, the coupling agent is one or more of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-aminopropyltriethoxysilane; further preferably, it is N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane.

[0050] Preferably, the mass ratio of the N-(β-aminoethyl)-γ-aminopropyltriethoxysilane to 3-mercaptopropyltriethoxysilane is 1:(0.5-2); further preferably, it is 1:1.

[0051] Preferably, the graphene oxide includes a first graphene oxide and a second graphene oxide.

[0052] Preferably, the weight ratio of the first graphene oxide to the second graphene oxide is 1:(0.5-2); further preferably, it is 2:3.

[0053] Preferably, the first graphene oxide has an average thickness of 0.5 to 1.2 nm, a diameter of 4 to 7 μm, and one layer.

[0054] Preferably, the second graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.

[0055] In some preferred embodiments, the first graphene oxide and the second graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0056] Preferably, the added amount of the coupling agent is 1%-2% of the mass of graphene oxide.

[0057] The inventors found that by selecting modified graphene oxide as inorganic particles, the wear resistance and impact resistance of plastic products can be improved without affecting the jade-like effect of plastic products, making plastic products more suitable for application in the field of high-end decoration. This may be because on the one hand, by compounding the first graphene oxide and the second graphene oxide with different numbers of layers and sizes, the first graphene oxide has a single-layer structure, a small average thickness and a suitable diameter, and can be used as a nanofiller to effectively fill the voids in the polymer matrix, reduce defects, and improve the density and overall strength of the material. Although the second graphene oxide has a slightly larger number of layers, its larger interlayer spacing and better dispersibility help to form more physical crosslinking points in the polymer, improve the toughness and impact resistance of the material, and the compound use of the two graphene oxides not only plays their respective advantages, but also achieves complementary performance through synergistic effects, thereby preparing modified graphene oxide with better comprehensive performance. On the other hand, by selecting N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane as coupling agents, their unique functional groups react chemically with the functional groups on the surface of graphene oxide, thereby introducing new active groups on the surface of graphene oxide, significantly enhancing the interfacial interaction between graphene oxide and the polymer matrix, and improving the compatibility and interfacial bonding between the two. This modification not only enhances the dispersion stability of graphene oxide in the polymer, but also promotes the uniform transmission of stress inside the material, thereby significantly improving the wear resistance and mechanical properties of plastic products. When this modified graphene oxide is added to the masterbatch as an inorganic particle and further used in the preparation of PP plastic products, its excellent dispersibility and interfacial bonding force enable the plastic products to maintain a good jade-like effect while significantly improving the wear resistance, scratch resistance, anti-aging performance and mechanical properties, broadening the application field of plastic products, especially in the field of high-end decoration. Competitiveness.

[0058] The method for preparing the masterbatch comprises the following steps: mixing the raw materials for preparing the masterbatch, adding the raw materials into a twin-screw extruder, and performing melt extrusion and granulation to obtain the masterbatch.

[0059] The temperatures of the first to fifth zones of the twin-screw extruder are 200-210° C., 210-220° C., 220-230° C., 220-230° C., and 230-240° C., respectively; and the rotation speed is 400-500 r / min.

[0060] Preferably, the compatibilizer includes MAH-g-PP and SMA.

[0061] Preferably, the mass ratio of MAH-g-PP to SMA is (1-3):1; more preferably, it is 2:1.

[0062] Preferably, the MAH-g-PP has a melt index of 30-40 g / 10 min at 190° C. and a MAH graft content of 0.8%-1.2%.

[0063] In some preferred embodiments, the MAH-g-PP is purchased from Dongguan Kangjin New Material Technology Co., Ltd.

[0064] Preferably, the maleic anhydride content in the SMA is 23%-27%, the weight average molecular weight is 7000-8000, the molar ratio of St to MAH is 2:1, and the acid value is 270-305 mgKOH / g.

[0065] In some preferred embodiments, the SMA is purchased from Guangdong Dingxin Polymer Technology Co., Ltd.

[0066] The inventors found that the use of specific MAH-g-PP and SMA as compatibilizers can improve the compatibility between PE and PMMA and PP, thereby improving the jade-like effect and mechanical properties of plastic products. This may be because MAH-g-PP and SMA work synergistically. On the one hand, the maleic anhydride functional groups of each interact with the polar groups in the polymer to form a multi-point cross-linked structure, which not only enhances the interfacial bonding force between the polymers, but also promotes the uniform distribution of stress inside the material. On the other hand, the styrene in SMA has good compatibility with the non-polar parts in PE and PP, further enhancing the stability and uniformity of the system. This synergistic effect makes the blend of masterbatch prepared from PE and PMMA and PP easier to plasticize and shape during processing, while improving the mechanical properties, heat resistance and chemical resistance of the product.

[0067] During the injection molding, the temperatures of each section of the injection molding machine are: barrel temperature: 220-240°C, nozzle temperature: 230-250°C, mold temperature: 50-70°C; injection pressure is 80-120MPa, injection speed is 50-70mm / s, holding time is 10-20s, and cooling time is 20-30s.

[0068] The second aspect of the present invention provides a product prepared by the spray-free process for the jade pattern.

[0069] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0070] 1. The present invention provides a jade pattern with stable contact performance. By preparing a specific masterbatch, adding functional additives, and combining molding technology, the final product can show a natural, smooth, and layered jade texture without using an additional spraying process. This method not only greatly simplifies the production process and reduces costs, but also avoids the environmental pollution problems that may arise in the traditional spraying process. In addition, the product prepared by the technical solution provided by the present invention has good mechanical strength, weather resistance, wear resistance, and color durability, and is suitable for high-end decorative materials and other fields.

[0071] 2. The present invention prepares masterbatch by selecting specific PE and PMMA as carrier resins, and applies it in the field of plastic products. It can achieve an effect similar to the texture of natural jade without using an additional spraying process, while ensuring the color presentation effect and the mechanical properties of the plastic products.

[0072] 3. The present invention can improve the compatibility between PE and PMMA and PP by selecting specific MAH-g-PP and SMA as compatibilizers, thereby improving the jade-like effect and mechanical properties of plastic products.

[0073] 4. The present invention uses specific ethylene-octene copolymers, methyl methacrylate-butadiene-styrene copolymers, and ethylene-vinyl acetate copolymers as toughening agents, which can enhance impact resistance and wear resistance while maintaining good weather resistance and jade-like effects.

[0074] 5. The present invention uses modified graphene oxide as inorganic particles, which can improve the wear resistance and impact resistance of plastic products without affecting the jade-like effect of plastic products, making the plastic products more suitable for application in the field of high-end decoration. DETAILED DESCRIPTION

[0075] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] The raw materials used in the present invention are all commercially available, specifically:

[0077] PP is homopolymer PP, with a melt index of 10-15 g / 10 min at 190° C., isotacticity ≥ 95.5%, and flexural modulus ≥ 1300 MPa, purchased from Dongguan Weicai Plastic Raw Materials Co., Ltd., PPH-M12.

[0078] The melt index of LLDPE at 190°C is 45-55g / 10min, and the density is 0.9-0.95g / cm 3 , Izod notch impact strength is 45-50kJ / m 2 , purchased from ExxonMobil, LL6201XR.

[0079] HDPE has a melt index of 28-32 g / 10 min at 190°C, a tensile yield stress ≥ 20 MPa, and a flexural modulus ≥ 950 MPa, and is purchased from ExxonMobil, HDPE HMA018.

[0080] PMMA has a melting index of 15-20 g / 10 min at 230°C, a total light transmittance of ≥92%, and a Rockwell hardness of ≥84. It was purchased from Qingdao Zhongxin Huamei Plastic Co., Ltd., CM-211.

[0081] The melt index of ABS at 200°C is 2-5g / 10min, the elongation is 35%-45%, and the bending strength is 600-650kg / cm 3 , purchased from Chi Mei, Taiwan, China, PA-726M.

[0082] The kinematic viscosity of oxidized polyethylene wax at 140°C is 20.5 mm 2 / s, softening point is 115℃, purchased from Henan Yuyang Wax Industry Co., Ltd.

[0083] The melt index of ethylene-octene copolymer at 190°C is 28-32 g / 10 min. It is preheated for 1 minute using a large rotor and rotated at 121°C for 4 minutes. The Mooney viscosity of the material is 1-3 MU and is purchased from Dow Chemical, USA, 8400.

[0084] The rubber content of methyl methacrylate-butadiene-styrene copolymer is 58%-62%, the hydroxyl value is 4-6phr, and the impact strength at 1 / 8 inch thickness is 73-75kJ / m 2 , purchased from Japan, M521.

[0085] The ethylene-vinyl acetate copolymer has a melt index of 2.5 g / 10 min at 190° C., a vinyl acetate content of 18%, and an elongation at break of 800 MPa. It was purchased from Formosa Plastics Corporation in Taiwan, China, and is EVA SF45TAISOX.

[0086] The first graphene oxide has an average thickness of 0.5 to 1.2 nm, a diameter of 4 to 7 μm, and 1 layer; the second graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers; both were purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0087] MAH-g-PP has a melt index of 30-40 g / 10 min at 190° C. and a MAH graft content of 0.8%-1.2%, and was purchased from Dongguan Kangjin New Material Technology Co., Ltd.

[0088] The maleic anhydride content in SMA is 23%-27%, the weight average molecular weight is 7000-8000, the molar ratio of St and MAH is 2:1, and the acid value is 270-305 mgKOH / g. It was purchased from Guangdong Dingxin Polymer Technology Co., Ltd.

[0089] Example 1

[0090] This embodiment provides a spray-free process for producing jade patterns, the steps of which are: mixing the raw materials evenly, performing injection molding, and polishing the surface to obtain the pattern.

[0091] The raw materials are base resin, masterbatch and compatibilizer.

[0092] The mass of the masterbatch is 10% of the mass of the base resin.

[0093] The added amount of the compatibilizer is 2% of the total mass of the base resin and the masterbatch.

[0094] The base resin is PP.

[0095] The masterbatch is prepared from raw materials, by weight, including 90 parts of carrier resin, 0.3 parts of colorant, 0.8 parts of antioxidant, 1 part of lubricant, 0.8 parts of light stabilizer, 4 parts of toughening agent, and 5 parts of inorganic particles.

[0096] The carrier resin is PE, PMMA and ABS, and the mass ratio is 1:1:1.

[0097] The PE is LLDPE and HDPE, and the mass ratio is 1:1.

[0098] The colorant is phthalocyanine blue B.

[0099] The antioxidants are antioxidant 1010 and antioxidant 168, with a mass ratio of 1:1.

[0100] The lubricant is oxidized polyethylene wax and calcium stearate, with a mass ratio of 2:1.

[0101] The light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0102] The toughening agent is ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, and ethylene-vinyl acetate copolymer, and the mass ratio is 2:2:1.

[0103] The inorganic particles are modified graphene oxide.

[0104] The preparation method of the modified graphene oxide comprises the following steps: hydrolyzing a coupling agent in an ethanol aqueous solution, adding graphene oxide, stirring at 60° C. for 2 hours, vacuum filtering, taking out powder, heating and drying to obtain the modified graphene oxide.

[0105] The mass fraction of ethanol in the ethanol aqueous solution is 15%.

[0106] The volume ratio of the coupling agent to the ethanol aqueous solution is 1:40.

[0107] The coupling agent is N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane, and the mass ratio is 1:1.

[0108] The graphene oxide includes a first graphene oxide and a second graphene oxide, and the weight ratio of the first graphene oxide and the second graphene oxide is 2:3.

[0109] The added amount of the coupling agent is 1.5% of the mass of graphene oxide.

[0110] The method for preparing the masterbatch comprises the following steps: mixing the raw materials for preparing the masterbatch, adding the raw materials into a twin-screw extruder, and performing melt extrusion and granulation to obtain the masterbatch.

[0111] The temperatures of zones 1 to 5 of the twin-screw extruder are 205° C., 215° C., 225° C., 225° C., and 235° C., respectively; and the rotation speed is 450 r / min.

[0112] The compatibilizers are MAH-g-PP and SMA, with a mass ratio of 2:1.

[0113] During the injection molding, the temperatures of each section of the injection molding machine are: barrel temperature: 230°C, nozzle temperature: 240°C, mold temperature: 60°C; injection pressure is 100MPa, injection speed is 60mm / s, holding time is 15s, and cooling time is 25s.

[0114] Example 2

[0115] The difference between this embodiment and embodiment 1 is that the mass of the masterbatch is 20% of the mass of the base resin.

[0116] Example 3

[0117] The difference between this embodiment and embodiment 1 is that the raw materials for preparing the masterbatch, by weight, include 120 parts of carrier resin, 0.3 parts of colorant, 0.8 parts of antioxidant, 1 part of lubricant, 0.8 parts of light stabilizer, 4 parts of toughening agent, and 6 parts of inorganic particles.

[0118] Comparative Example 1

[0119] The difference between this comparative example and Example 1 is that the mass of the masterbatch is 25% of the mass of the base resin.

[0120] Comparative Example 2

[0121] The difference between this comparative example and Example 1 is that the carrier resin is PE and ABS, and the mass ratio is 1:1.

[0122] Comparative Example 3

[0123] The difference between this comparative example and Example 1 is that the PE is LLDPE.

[0124] Comparative Example 4

[0125] The difference between this comparative example and Example 1 is that the toughening agent is ethylene-octene copolymer and methyl methacrylate-butadiene-styrene copolymer, and the mass ratio is 1:1.

[0126] Comparative Example 5

[0127] The difference between this comparative example and Example 1 is that the coupling agent is N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0128] Comparative Example 6

[0129] The difference between this comparative example and Example 1 is that the graphene oxide is the first graphene oxide.

[0130] Comparative Example 7

[0131] The difference between this comparative example and Example 1 is that the compatibilizer is MAH-g-PP.

[0132] Performance Testing

[0133] The cantilever beam room temperature notched impact strength of plastic products was tested with reference to the method in ASTM D256-10 (2018); Imitation jade effect test: The imitation jade texture effect was rated with reference to the method in patent CN 117866374A, with 1 being the worst and 5 being the best. The number of ratings was 10, and the average value was taken; The color uniformity of the product surface was measured using a colorimeter, and the color difference ΔE<0.5 indicated good coloring effect; Weather resistance test: The product was placed in a xenon lamp aging test chamber to simulate natural light conditions, and the color difference change after 1000 hours was tested. The color difference ΔE<1.0 indicated good color durability and good weather resistance; The Rockwell hardness of the product was tested, and high hardness indicated good wear resistance. The results are shown in Table 1.

[0134] Table 1 Measurement results

[0135] Impact strength J / m Imitation jade texture Color difference ΔE Weather resistance ΔE hardness Example 1 748 4.8 0.42 0.76 88 Example 2 739 4.5 0.50 0.93 84 Example 3 742 4.6 0.38 0.77 86 Comparative Example 1 614 3.9 0.88 1.92 80 Comparative Example 2 645 3.6 0.95 1.84 81 Comparative Example 3 672 4.0 0.66 1.61 82 Comparative Example 4 701 4.3 0.77 1.86 78 Comparative Example 5 725 4.5 0.68 1.57 77 Comparative Example 6 722 4.4 0.62 1.46 79 Comparative Example 7 584 3.8 0.97 2.28 75

[0136] According to statistics, the plastic products prepared by Examples 1 to 3 of the present invention have high impact strength, imitation jade texture on the surface, high color rendering and color durability, and excellent weather resistance and wear resistance. In Example 1, the masterbatch is added excessively, Example 2 does not add PMMA as a carrier, Example 3 does not add HDPE as a carrier, Example 4 does not add ethylene-vinyl acetate copolymer as a toughening agent, Example 5 does not add 3-mercaptopropyltriethoxysilane as a coupling agent, Example 6 does not add a second graphene oxide, and Example 7 does not add SMA as a compatibilizer. The mechanical properties, color rendering effect, imitation jade effect, weather resistance, and hardness of the prepared plastic products are poor. Therefore, the plastic products prepared by the raw materials and methods described in this application can show a natural, smooth, and layered jade texture without using an additional spraying process, and have good mechanical strength, weather resistance, wear resistance, and color durability.

[0137] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A spray-free process for jade patterns, characterized in that: The steps include: mixing the raw materials uniformly, injection molding, and polishing the surface; The raw materials include base resin, masterbatch and compatibilizer; The masterbatch is prepared from raw materials, by weight, including 60-120 parts of carrier resin, 0.1-0.5 parts of colorant, 0.5-1 parts of antioxidant, 0.5-1.5 parts of lubricant, 0.5-1 parts of light stabilizer, 2-5 parts of toughening agent, and 3-8 parts of inorganic particles; The carrier resin includes one or more of ABS, PP, PE, PS, and PMMA; The PE includes LLDPE and HDPE; The LLDPE has a melt index of 45-55 g / 10 min at 190°C and a density of 0.9-0.95 g / cm 3 , Izod notch impact strength is 45-50kJ / m 2 ; The HDPE has a melt index of 28-32 g / 10 min at 190° C., a tensile yield stress of ≥20 MPa, and a flexural modulus of ≥950 MPa; The PMMA has a melting index of 15-20 g / 10 min at 230° C., a total light transmittance of ≥92%, and a Rockwell hardness of ≥84.

2. The spray-free process of jade lines according to claim 1, characterized in that, The mass of the masterbatch is 1%-20% of the mass of the base resin; the added amount of the compatibilizer is 1%-3% of the total mass of the base resin and the masterbatch.

3. The spray-free process of jade lines according to claim 2, characterized in that, The base resin includes one or more of PA, PP, PC, HIPS, ABS, PMMA, ABS / PMMA, TPU, PBT, and POM.

4. The spray-free process of jade lines according to claim 3, characterized in that, The PP is homopolymer PP, with a melt index of 10-15 g / 10 min at 190° C., an isotacticity of ≥95.5%, and a flexural modulus of ≥1300 MPa.

5. The spray-free process of jade patterns according to claim 1, characterized in that, The toughening agent includes one or more of ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, ethylene-vinyl acetate copolymer, and ethylene-acrylate-glycidyl methacrylate terpolymer.

6. The spray-free process for jade patterns according to claim 1, characterized in that: The inorganic particles include one or more of modified graphene oxide, talc, montmorillonite, kaolin, titanium dioxide, silicon dioxide, and calcium carbonate.

7. The spray-free process for jade patterns according to claim 6, characterized in that: The preparation method of the modified graphene oxide comprises the following steps: taking a coupling agent and hydrolyzing it in an ethanol aqueous solution, then adding graphene oxide, stirring at 55-65° C. for 1-3 hours, vacuuming and filtering to take out the powder, heating and drying to obtain the modified graphene oxide.

8. The spray-free process for jade patterns according to claim 7, characterized in that: The compatibilizer includes MAH-g-PP and SMA.

9. The spray-free process for jade patterns according to claim 8, characterized in that: The MAH-g-PP has a melt index of 30-40 g / 10 min at 190° C., and a MAH graft content of 0.8%-1.2%. The SMA has a maleic anhydride content of 23%-27%, a weight average molecular weight of 7000-8000, a molar ratio of St to MAH of 2:1, and an acid value of 270-305 mgKOH / g.

10. A product prepared by the spray-free process for producing jade patterns according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Spraying-free aesthetic resin composition with amber effect and preparation method thereof

    CN103232640A

  • Spraying-free aesthetic resin with white jade effect and preparation method of aesthetic resin

    CN104403256A

  • Spraying-free aesthetic resin composition with bowlder effect and preparation method thereof

    CN104479283A

  • High-gloss spray-coating-free PMMA / ASA alloy resin composition and preparation method thereof

    CN105419205A

  • Spraying-free metal-effect ABS composite material for improving flow marks for air conditioner and preparation method of ABS composite material

    CN107400324A